2012
DOI: 10.1071/wf09065
|View full text |Cite
|
Sign up to set email alerts
|

Exploring phosphate effects on leaf flammability using a physical chemistry model

Abstract: Some plants have traits that cause them to be more flammable than others, influencing wildfire spread and fire regimes. Some of these plant traits have been identified through laboratory-scale experiments. We built a numerical model that could quantify the extent of these effects on flammability. Here we present that model and use it to investigate the effect of phosphate content on the flammability of leaves. The model used finite-element methods and was based on heat transfer and thermal decomposition kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Our results concur with the conclusion of Scarff et al . (), that effects of P on flammability are likely to be modest relative to those of leaf moisture content. They are also consistent with findings in southern Australian woodlands, that soil fertility could weakly influence fuel accumulation and flammability, but that rainfall was the dominant influence on fire regimes (Gibson et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results concur with the conclusion of Scarff et al . (), that effects of P on flammability are likely to be modest relative to those of leaf moisture content. They are also consistent with findings in southern Australian woodlands, that soil fertility could weakly influence fuel accumulation and flammability, but that rainfall was the dominant influence on fire regimes (Gibson et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Our measurements therefore represent the maximum potential flammability of litter and grass fuels at each site. It has also been suggested that soil nutrients, especially phosphorus, could influence flammability through their effects on plant growth, as well as phosphate being a fire retardant (Scarff et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…; Plucinski et al . ; Scarff, Gray & Westoby ). However, the role of interspecific variation in leaf traits in the different phases of a fire deserves more attention (Schwilk & Caprio ; de Magalhães & Schwilk ).…”
Section: Introductionmentioning
confidence: 99%
“…In litterbeds, leaf size is a dominant driver of different flammability parameters by influencing the packing (Scarff & Westoby 2006; van Altena et al 2012;Engber & Varner 2012; de Magalhães & Schwilk 2012), while leaf traits such as thickness, moisture content, phosphorus content and secondary chemistry (lignin, terpenoids) are deemed to play important roles as well (Montgomery & Cheo 1971;Ormeño et al 2009;Plucinski et al 2010;Scarff, Gray & Westoby 2012). However, the role of interspecific variation in leaf traits in the different phases of a fire deserves more attention (Schwilk & Caprio 2011;de Magalhães & Schwilk 2012).…”
mentioning
confidence: 99%
“…Soil P availability may directly influence leaf flammability by allowing plants to increase the uptake and retention of P into their foliar tissues (Tissue and Lewis 2010). Foliar P acts as a flame retardant to reduce flammability (Scarff and Westoby 2008;Scarff et al 2012) and increases litter decomposition rates (Vitousek 1998;Wardle et al 2002). In grasslands throughout the world, it is common for soil P availability to constrain aboveground biomass production (Elser et al 2007;Craine and Jackson 2010), therefore influencing fuel load accumulation.…”
Section: Introductionmentioning
confidence: 99%